APAKAH YANG MEMPENGARUHI KONSUMEN MUSLIM MEMBELI PRODUK MAKANAN IMPOR DALAM KEMASAN - Makfirah, Fajar; Umuri, Khairil (universitas teuku umar, 2023)
Global economic developments have made it easy for imported packaged food products to enter Indonesia. Specifically, this study explores the determinants related to decision making made by Muslim consumers buying packaged imported food products. The sample in this study was 100 respondents who were taken using a purposive sampling technique. Based on multiple linear regression, it is noted that the decision to buy imported food products is simultaneously determined by the variable halal labeling, price, and religiosity. Partially, only halal labeling does not affect purchasing decisions on packaged imported food products. Meanwhile, price and religiosity influence purchasing decisions on packaged imported food products. This empirical evidence shows that halal labeling has not been the focus of Muslim consumers in buying packaged imported food products. This becomes an important issue because consuming halal food is an obligation for a muslim.